The impact of Blockchain adoption on supply chain performance: evidence from food industry - Vu, Nam; Ghadge, Abhijeet; Bourlakis, Michael (Taylor & Francis, 2025)
The food supply chain (FSC) constantly needs to address persistent challenges such as information asymmetry, low transparency, food quality and authenticity, and unnecessary waste. Blockchain is perceived as a promising solution to overcome these FSC challenges. Existing literature captures a conceptual understanding of various aspects of Blockchain for FSC, such as how the technology can enhance transparency, efficiency, and food authenticity. However, a quantitative assessment of the overall impact of Blockchain adoption on the FSC operational performance is still missing. This study combines empirical and analytical approaches to investigate the evident research gap. Under the lens of systems thinking and System Dynamics (SD) modelling perspective, the study collected questionnaire and interview data to develop different FSC models for evaluating the impact of Blockchain on key operational performance metrics. The findings indicated that Blockchain positively affects inventory level and lead time in the immediate term, and cost in the long term. The results also warn that forgoing inventory buffers can come with the cost-of-service level. This study provides quantitative evidence of the positive influence of Blockchain on the FSC. This research contributes by extending the understanding of Blockchain's implications on broader supply chain performance from a systems perspective.
Keywords: Operations Research